Comprensión lectora y hábitos de estudio en estudiantes del primer grado de secundaria Institución Educativa Mariscal Oscar Raymundo Benavides Iquitos 2022 - Tello Pinedo, Norka Stephanie (2025)
The present study was aimed at confirming the connection between reading comprehension and study habits in first-grade secondary school students of a public Educational Institution in Iquitos, during the year 2022. It was carried out under a confirmatory quantitative methodology, using a correlational, non experimental transectional design. It was made up of 211 participants, selected through proportional and random sampling, to whom two questionnaires were administered that facilitated the evaluation of the analyzed variables. The findings of the study revealed that the level of reading comprehension is positively and significantly associated with reading habits in first grade high school students, with a Spearman's Rho coefficient of 0.669. This finding supports the main hypothesis of the research. On the other hand, the detailed analysis revealed a relevant connection between the literal level and study habits, with a Spearman's Rho of 0.659, supporting specific hypothesis 1. An important connection was also identified between the inferential level and study habits, with a Spearman's Rho of 0.662, validating specific hypothesis 2. Finally, the study showed a significant link between the critical level and study habits, with a Spearman's rho of 0.685, supporting specific research hypothesis 3.